Prolonged Analgesia With Liposomal Bupivacaine in a Mouse Model. Issue 4 (July 1994) - Grant, Gilbert J.; Vermeulen, Kristien; Langerman, Lev; Zakowski, Mark; Turndorf, Herman
Abstract : Background and Objectives: Currently available local anesthetics have relatively limited duration of action and some may cause severe systemic toxicity. An ultralong lasting local anesthetic would be useful to produce prolonged intraoperative anesthesia and extended postoperative analgesia. The goal of this study was to synthesize a sustained release local anesthetic formulation that would produce prolonged sensory block and decrease the possibility of systemic toxicity. Methods: The effect of liposomes containing 1.1% bupivacaine on duration of sensory block of the mouse tail was compared with equivalent concentrations of bupivacaine with and without epinephrine. Analgesia was assessed using the tail flick test. Systemic toxicity (LD50) was assessed after intraperitoneal injection and in vitro release rates were compared by dialysis technique for liposomal and plain bupivacaine. Results: Sensory block was significantly prolonged with liposomal bupivacaine (130 ± 38 minutes) compared to plain bupivacaine (46 ± 11 minutes, P < .01) or bupivacaine with epinephrine (81 ± 28 minutes, P < .05). The LD50 was significantly lower for plain bupivacaine (61 mg/kg, 95% confidence intervals 47-79) than for liposomal bupivacaine (291 mg/kg, 95% confidence intervals 201-422). The time to 50% in vitro release through a dialysis membrane for liposomal bupivacaine (28 ± 9 minutes) was markedly prolonged compared to plain bupivacaine (7 ± 1 minutes). Conclusions: This study shows that liposomal encapsulation of bupivacaine significantly prolongs duration of action and greatly decreases systemic toxicity of the drug. These findings may be promising for the future production of formulations of ultralong lasting local anesthetics with enhanced efficacy and safety.